Dampak Non-Debt Tax Shield dan Resiko Bisnis Terhadap Struktur Modal Perusahaan Manufaktur Indonesia - Ani Wilujeng Suryani; Mitha Icha Sari (Ekonomi Bisnis, 2020)
Capital structure decision is an important act made by company’s financial manager as mismanagement causes financial distress. This study aims to determine the effect of non-debt tax shield and business risk on capital structure. The data in this study were collected from the financial reports of 137 manufacturing companies in Indonesia from 2014 to 2019. Hypothesis testing was carried out using a fixed effect panel regression model. The results showed that the non-debt tax shield had a significant negative effect on capital structure, while business risk had a positive effect. Thus, companies that have a low non-debt tax shield will increase their debt to get compensation for tax deductions from interest expenses, while companies with a high risk level prefer internal financing to decrease the debt level. This study contributes to the literature by uncovering the factors that influence the determination of corporate debt levels in manufacturing industries in Indonesia. The result of this research can be used by the company managers to consider business risk and non-debt tax shields in determining the optimum capital structure to increase the value of the company.